1999
DOI: 10.1038/7610
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The structures of functional peptides corresponding to the predicted channel-lining M2 segments of the nicotinic acetylcholine receptor (AChR) and of a glutamate receptor of the NMDA subtype (NMDAR) were determined using solution NMR experiments on micelle samples, and solid-state NMR experiments on bilayer samples. Both M2 segments form straight transmembrane alpha-helices with no kinks. The AChR M2 peptide inserts in the lipid bilayer at an angle of 12 degrees relative to the bilayer normal, with a rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
360
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(372 citation statements)
references
References 39 publications
12
360
0
Order By: Relevance
“…50% of the total protein, the ␣-helical content of about 25% derived from our CD and FTIR-data would correspond to a portion of about 12% of the full-length ␣1 subunit. Given that the helical structure of TM2 (8,9,15,40) contributes a further 5%, a total of at least 17% ␣-helical structure would be expected for the entire GlyR ␣1 subunit. This is in qualitative agreement with the prediction of about 15% ␣-helical content for the reconstituted GlyR ␣1-subunit (41) or its fragment ␣1-(165-291) (42).…”
Section: Functional Refolding Of Isolated Glyr Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…50% of the total protein, the ␣-helical content of about 25% derived from our CD and FTIR-data would correspond to a portion of about 12% of the full-length ␣1 subunit. Given that the helical structure of TM2 (8,9,15,40) contributes a further 5%, a total of at least 17% ␣-helical structure would be expected for the entire GlyR ␣1 subunit. This is in qualitative agreement with the prediction of about 15% ␣-helical content for the reconstituted GlyR ␣1-subunit (41) or its fragment ␣1-(165-291) (42).…”
Section: Functional Refolding Of Isolated Glyr Domainsmentioning
confidence: 99%
“…A large cytosolic loop, flanked by TM3 and TM4, is thought to mediate intracellular interactions. Based on NMR studies of corresponding synthetic peptides, TM2 of the nAChR and GlyR has been demonstrated to be ␣-helical (8,9). Several attempts have been made to elucidate the structure of the nAChR extracellular domain, which is widely seen as a prototype of the structural homologous GlyR.…”
mentioning
confidence: 99%
“…Recent developments in bacterial expression systems for the preparation of recombinant isotopically labeled membrane proteins, methods for sample preparation, pulse sequences for high-resolution spectroscopy, and structural indices that guide the structure assembly process, have greatly extended the capabilities of these techniques, and the structures of a variety of helical membrane proteins have been determined by NMR in micelles and in bilayers [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of binding to DPC micelles and lipid II on the mersacidin dynamics are characterized by means of 15 N relaxation together with gradient-edited diffusion experiments. Despite the large number of published solution NMR structural and relaxation dynamics studies of membrane proteins and peptides (12)(13)(14)(15)(16), only a few examples of high resolution NMR studies of protein/peptide-ligand interactions in the presence of membrane-like environments are available to date (17,18). We will show that the differences in sample environments result in substantial conformational changes that modulate the charge accessibility.…”
Section: In Dodecylphosphocholine (Dpc)mentioning
confidence: 99%